2015
DOI: 10.1002/aic.14800
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic mechanism of free heme action on sickle cell hemoglobin polymerization

Abstract: For insights into the mechanisms of heme action on the rate of sickle cell hemoglobin polymerization, we determine the erythrocytic concentration of free heme using a novel method based on enzymatic catalysis and luminescence. We find in sickle cell patients 44 6 10 mM, in sickle trait individuals, 33 6 4 mM, and in healthy adults, 21 6 2 mM. We test the applicability of two mechanisms of heme action: a kinetic one, whereby heme aggregates serve as heterogeneous nucleation centers, and a thermodynamic pathway,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 101 publications
(131 reference statements)
3
5
0
Order By: Relevance
“…Note that these values of the hematin concentration in the cells are not directly read from the calibration curve in Figure C because the cell hemolysates were diluted by 183 times due to the high concentration of hematin in erythrocytes (the evaluation of dilution ratio of the hemolysate is described in the Supporting Information). These results are similar to those previously reported, for example, Aich et al reported that the concentrations of hematin in sickle cells and healthy erythrocytes are 44 ± 10 and 21 ± 2 μM, , respectively, and Liu et al reported that the hematin concentration in sickle cells is 3–5 times the value of healthy erythrocytes . These results show that the fabricated biosensor can be employed as a practical platform for hematin quantification in erythrocytes.…”
Section: Results and Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Note that these values of the hematin concentration in the cells are not directly read from the calibration curve in Figure C because the cell hemolysates were diluted by 183 times due to the high concentration of hematin in erythrocytes (the evaluation of dilution ratio of the hemolysate is described in the Supporting Information). These results are similar to those previously reported, for example, Aich et al reported that the concentrations of hematin in sickle cells and healthy erythrocytes are 44 ± 10 and 21 ± 2 μM, , respectively, and Liu et al reported that the hematin concentration in sickle cells is 3–5 times the value of healthy erythrocytes . These results show that the fabricated biosensor can be employed as a practical platform for hematin quantification in erythrocytes.…”
Section: Results and Discussionsupporting
confidence: 91%
“…Liu and co-workers have reported a method based on the absorption characteristics of hematin to assay hematin in healthy and sickle erythrocytes after separating hematin from Hb by ion-exchange liquid chromatography . Aich and co-workers reported an enzymatic catalysis-based chemiluminescence method to quantify hematin in healthy human erythrocytes after isolation from Hb in lysed erythrocytes by dialysis. , Although the two methods are effective, they are time-consuming, since several tedious steps are required to separate hematin from Hb before the assay.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They conclude that the rate-determining step of the assembly phase is assembly nucleation, which is controlled by both viscosity and monomer concentration of the metastable phase. Since the amount of the metastable phase significantly impacts the maturation of the assembly phase, Kashchiev and co-workers simulated the assembly nucleation rate as a function of the individual metastable particle size . Later Auer et al compared the difference between 1SN and 2SN using classical nucleation theory to simulate the formation of the metastable phases.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, models have been developed in which the sizes of the individual oligomeric phases dictate the assembly nucleation rate (Scheme ). ,, To demonstrate the importance of the nucleation rates, Auer et al compared the one-step and two-step nucleation models for assembly of amyloid fibrils and concluded that while two-step nucleation best explains the observed assembly kinetics, one-step nucleation may contribute to the nucleation kinetics in some assemblies …”
Section: Mechanisms Of Nucleation and Propagation In Biopolymer Conde...mentioning
confidence: 99%